Green synthesis of silver nanoparticles using Nardostachys jatamansi and evaluation of its anti-biofilm effect against classical colonizers. (January 2019) - Muthuraman, Meenakshi Sundaram; Nithya, S.; Vinoth kumar, V.; Christena, Lowrence Rene; Vadivel, Vellingiri; Subramanian, Nagarajan Sai; Anthony, Savarimuthu Philip
Abstract: In this communication, we present the green synthesis of silver nanoparticles (AgNPs) using medicinally important Nardostachys jatamansi rhizome extract in the presence of sunlight. UV–vis spectroscopy, Fourier Transform Infrared spectroscopy (FTIR), Transmission electron microscope (TEM) and Energy dispersive X-ray analysis (EDX) were employed to characterize the synthesized AgNPs. UV–visible spectroscopic studies confirmed the presence of biosynthesized AgNPs. Transmission Electron Microscopic studies revealed the structure of spherical AgNPs in the diameter range of 10–15 nm. Energy dispersive X-ray analysis and elemental mapping clearly confirmed the presence of silver in AgNPs samples. Interestingly, biomolecules functionalised AgNPs exhibited a remarkable antioxidant, anti-inflammatory, and anti-biofilm activities and hence biosynthesized AgNPs from N. jatamansi can be used as a promising biomaterial for biomedical applications. Highlights: Green synthesis of AgNPs using Nardostachys jatamansi rhizome extract. Biogenic AgNPs was found to be spherical in the size range of 10–15 nm. AgNPs exhibited significant anti-biofilm effect against classical colonizers.